Al-Farabi: Politik sebagai Jalan Kebahagiaan - Jamalul Muttaqin; Syamsiyani (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
Political polemics were always hot among politicians, academics and others. It was not uncommon to become a national discussion to achieve common good. Listening to politics, the monumental figure of the Islamic Philosopher, al-Farabi, was one of the most famous figures to be studied in depth, especially in terms of his thoughts in the book `Ara Ahl al Madinah. The purpose of this study was to explore al-Farabi's thoughts about politics as the goal of happiness, that a country would be ideal if its leaders and people were like a complete body. In order for all its organs to work together well, it would also give birth to a good country. The method used was descriptive qualitative research. This study described al-Farabi's thoughts in the political field. The author tried to take the red thread from al-Farabi's political thoughts as the ecstasy of happiness, especially for human life universally.